Integrasi Komunikasi Refleksi Mingguan Untuk Pengembangan Moral Etika Dan Efektivitas Pengelolaan Kelas - Haryanto, Jennifer; Vincentius Jimnie (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2025)
The transition from elementary to junior high school is a critical phase often marked by emotional instability, low ethical awareness, and a decline in students’ communication skills. This study aims to examine the effectiveness of weekly reflections integrated with classroom teacher–student communication as a strategy for developing moral and ethical character to foster conducive classroom management. A mixed-method approach was employed, with data collected through observation, daily reflections, and Google Form questionnaires. The findings indicate that consistent weekly reflections encourage improvements in students’ self-awareness, critical thinking, and self-control. This study underscores that the integration of reflection and communication is a strategic and effective approach to shaping new student habitus during the transition period.